2019
DOI: 10.1021/acs.joc.9b00834
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Electron Demand Diels–Alder Reactions of Heterocyclic Azadienes, 1-Aza-1,3-Butadienes, Cyclopropenone Ketals, and Related Systems. A Retrospective

Abstract: A summary of the investigation and applications of the inverse electron demand Diels–Alder reaction is provided that have been conducted in our laboratory over a period that now spans more than 35 years. The work, which continues to provide solutions to complex synthetic challenges, is presented in the context of more than 70 natural product total syntheses in which the reactions served as a key strategic step in the approach. The studies include the development and use of the cycloaddition reactions of hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 462 publications
(377 reference statements)
1
55
0
Order By: Relevance
“…Bioorthogonal reactions have become increasingly important to chemistry and biology since the term was initially coined early in this century. [1] Thebioorthogonal reactions of tetrazines have become widely used in various fields, [2] including natural product synthesis, [3] cargo delivery, [4] genetic code expansion, [5] fluorogenic labeling, [6] radiochemistry, [7] coordination chemistry, [8] and material science. [9] Coupled to the growing utility of tetrazine-based bioorthogonal chemistry is the need for mild, safe,a nd general methods of introducing tetrazine groups to complex molecules.C arboxylic esters are ubiquitous functional groups that have been used as handles for the introduction of preformed tetrazine groups through amide bond forming reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Bioorthogonal reactions have become increasingly important to chemistry and biology since the term was initially coined early in this century. [1] Thebioorthogonal reactions of tetrazines have become widely used in various fields, [2] including natural product synthesis, [3] cargo delivery, [4] genetic code expansion, [5] fluorogenic labeling, [6] radiochemistry, [7] coordination chemistry, [8] and material science. [9] Coupled to the growing utility of tetrazine-based bioorthogonal chemistry is the need for mild, safe,a nd general methods of introducing tetrazine groups to complex molecules.C arboxylic esters are ubiquitous functional groups that have been used as handles for the introduction of preformed tetrazine groups through amide bond forming reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in the activation enthalpies caused by the effects of substituents at the 3-position are similar to the trends in reactivity previously reported in inverse electron-demand Diels–Alder reactions with tetrazines and triazines. 51 …”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Limitations of this conceptually interesting synthesis of pyridines are the high temperature (up to 280 °C under classical conditions 6 ) and very long reaction times that are required [7][8][9] to overcome the intrinsic lack of reactivity of these aza-dienes. [10][11][12][13][14][15][16][17][18][19] On the other hand, we recently reported that pyrimidines substituted in the 2-position by an (alkynyl)hydrazone could be exceptionally activated towards intramolecular [4ps+2ps] cycloadditions by a simple activation (Scheme 1, A). 20 In a practical one-pot procedure starting from 2-hydrazinopyrimidine 2, it was shown that condensation with ynone 3 in the presence of catalytic amount of trifluoroacetic acid was rapid at 60 °C in THF, leading to hydrazone 4a.…”
Section: Introductionmentioning
confidence: 99%